2016
DOI: 10.1371/journal.pone.0163530
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate Stimulates Differentiation, Matrix Gene Expression and Alkaline Phosphatase Activity in Osteoblasts

Abstract: Pyrophosphate is a potent mitogen, capable of stimulating proliferation in multiple cell types, and a critical participant in bone mineralization. Pyrophosphate can also affect the resorption rate and bioactivity of orthopedic ceramics. The present study investigated whether calcium pyrophosphate affected proliferation, differentiation and gene expression in early (MC3T3 pre-osteoblast) and late stage (SAOS-2 osteosarcoma) osteoblasts. Pyrophosphate stimulated peak alkaline phosphatase activity by 50% and 150%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 49 publications
3
52
0
1
Order By: Relevance
“…1C). We then examined the early osteogenic markers ALP [17,62,63] and mineral node formation. ALP activity was analyzed by histochemical staining.…”
Section: Resultsmentioning
confidence: 99%
“…1C). We then examined the early osteogenic markers ALP [17,62,63] and mineral node formation. ALP activity was analyzed by histochemical staining.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent study has shown that high extracellular Pi induced phenotypic transformation of vascular smooth muscle cells into osteogenic-like cells via the activation of Wnt/β-catenin signaling in these cells [42]. Our previous study, however, also suggested that extracellular PPi directly stimulates osteogenesis [2, 43]. Therefore, it is possible that extracellular PPi resulting from ANK transport directly or via its hydrolysis to extracellular Pi may affect Wnt/β-catenin signaling in osteogenic precursor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Cells differentiation into osteoblasts was investigated by ALP assay that is a marker of early stages of osteogenic differentiation. ALP plays a role in the conversion of inorganic pyrophosphate into inorganic phosphate, a process that promotes the formation of bone matrix, before the mineralization process [44]. Over a period of 14 days, all the studied hydrogels promoted cell differentiation at the same level.…”
Section: Discussionmentioning
confidence: 96%